Development and feasibility of a web‐based question prompt sheet to support information provision of health‐related quality of life topics after oesophageal cancer surgery. (13th October 2016) - Jacobs, M.; Henselmans, I.; Arts, D. L.; ten Koppel, M.; Gisbertz, S. S.; Lagarde, S. M.; van Berge Henegouwen, M. I.; Sprangers, M. A. G.; de Haes, H. C. J. M.; Smets, E. M. A.
Abstract : We developed a web‐based question prompt sheet (QPS) to support information provision of health‐related quality of life (HRQL) topics after oesophageal cancer surgery. The QPS was evaluated and updated in three consecutive studies. In Study 1, eight patients were guided in using the QPS. Feasibility was assessed by cognitive walkthrough, questionnaire and interview. We obtained 430 notes (217 negative, 213 positive) of patients' actions and or remarks, and 91 suggestions. With minor support, most patients were able to use the QPS. In Study 2, forty patients independently used and appraised a modified version of the QPS by questionnaire. All patients deemed the QPS to be usable and useful. In Study 3, 21 patients and three surgeons used the QPS in clinical practice. Clinical feasibility was assessed by the number of QPS sent to the researcher/surgeon. Patients and surgeons were surveyed and the follow‐up consultation was audio‐recorded. Surgeons were additionally interviewed. Twenty/fourteen patients sent their QPS to the researcher/surgeon. Five QPSs were read by the consultation surgeon. Patients considered the QPS usable and useful. Surgeons considered the QPS of added value and helpful in informing patients, but currently not clinically feasible due to increased consultation time.